Discounted Labour : Women Workers in Canada, 1870-1939 - Frager, Ruth A., 1950-; Patrias, Carmela, 1950- (Book collections on Project MUSE., 2015)
Discounted Labour is an essential new work for anyone interested in the historical struggle for gender equality in Canada.